Reuse of nitric acid in the oxidative pretreatment step for preparation of humic acids from low rank coal of Mukah, Sarawak - Sim Siong, Fong; Lau, Seng; Haslinda, Mat (SciELO Publishing, 2007)
Nitric acid is an effective material for production of humic acids. Nevertheless, it is an expensive item that renders the process unfavorable industrially. Study indicated that there was a possibility to reuse the nitric acid for oxidation however the resulting structures of humic acids was not studied. Therefore, the objective of this study was to investigate the chemical and spectroscopic properties of nitrohumic acids prepared with reused nitric acid. The coal sample was oxidized with 5%, 10% and 15% of nitric acid and subjected to extraction for nitrohumic acids. Concentration of nitric acid with the most yields was reemployed for another 2 cycles of oxidation. The chemical and spectroscopic properties of nitrohumic acids were evaluated. The results indicated that oxidation process generally improved the acidic functional properties of the nitrohumic acids with 10% nitric acid producing the most promising yield. The nitric acid was reused for extraction and the percentage yield remained good at an average of 78%. Structurally, the nitrohumic acids produced with the reused nitric acid demonstrated larger molecular size and fewer acidic functional groups suggesting lesser extent of structure fractionation.